Simuliidae (insecta: diptera) de colombia iii - descripción de una nueva especie de gigantodax enderlein, 1925 (1981)
A description of all stages of development of a new species of the high Andes of Colombia, of the genus Gigantodax. The material was collected in the río Teusacá, La Calera, Cundinamarca.